Üniversite Öğrencilerinin Vatandaşlık Algısının Belirlenmesi - Demi̇rbaş, İbrahim; Aydinözü, Duran (Kastamonu Egitim Dergisi, 2020)
In this thesis, it is aimed to determine the citizenship behaviours of Kastamonu University students’ based on certain variables. In order to prepare the questionnaire of this study, expert opinions were applied at the first stage. After a pilot implementation was carried out, the questionnaire was submitted to experts’ opinions again and the final form of the questionnaire was generated in the framework of the feedbacks. The population of the study includes 20.476 students studying at the university between 2014-2015 academic year. The sample contains 1909 students chosen from this population. The data were collected using five-point Likert-type Citizenship Perception Scale. The scale consists of two sections, five factors and 45 items. While the first section includes demographic information, the second sections includes items about citizenship perception. In order to analyse the data, SPSS (Statistical Package for Social Science) software was used. The findings showed that citizenship perceptions of university students differentiate according to the gender. The citizenship perceptions of the female students were found to be higher than the males’. Additionally, the citizenship perceptions of the students living in the city centre were higher than the ones living in the villages. In accordance with these findings it is thought that the reason for the female students’ higher citizenship perceptions may be investigated. Besides, the reason that the citizenship perceptions of the students living in the villages were lower than the ones living in the city centre may be researched in w new study.
Keywords: sosyal bilgiler; vatandaşlık; vatandaşlık algısı; vatandaşlık eğitimi; Eğitim Üzerine Çalışmalar; Studies on Education; social studies; citizenship; citizenship perception; citizenship education; 4. Education